Evaluation of the effect of hypnobirthing education during antenatal period on fear of childbirth - Bülez, Aysel; Çeber Turfan, Esin; Soğukpınar, Neriman (The European Research Journal, 2019)
Objectives: The objective of this research was to analyse the effect of hypnobirthing education given to pregnant women during antenatal period on fear of childbirth. Methods: This is an educational interventional case-control study. A total of 51 pregnant women were studied together during the 12th week of pregnancy. Ethical Committee and related consents were taken. Data was evaluated by using descriptive statistics. Results: The age average of the pregnant in the control group was 28.70 ± 5.42 years while it was 25.74 ± 5.16 years for the case group. Women’s gestational week averages were 20.87 weeks for study and 24.10 weeks for control group. In the study, the pre-training scale scores of the cases and control groups were compared with the average level of birth fear of the groups (t = 1.848, p = 0.073). There was a significant difference between pre- and post-hypnotic scale scores in the birth preparation class (t = -5.329, p < 0.001). Before the training; 48% of the case group. Fifty-two percent of the control group is adequately informed about the hypnobirthing problem. Conclusions: It was found that among the pregnant women who had attended birth preparation classes, positive labour perception of the intervention group pregnant women was higher than that of the control group pregnant women who hadn’t had hypnobirthing education and there was a significant difference between them.